Albumins represent highly cross-reactive animal allergens - Liu, Zicheng; Trifonova, Daria; Tulaeva, Inna; Riabova, Ksenja; Karsonova, Antonina; Kozlov, Evgeny; Elisyutina, Olga; Khaitov, Musa; Focke-Tejkl, Margarete; Chen, Ting-Huan; Karaulov, Alexander; Valenta, Rudolf (Frontiers in Immunology, 2023)
Albumins from animals are highly cross-reactive allergens for patients suffering from immunoglobulin E (IgE)-mediated allergy. Approximately 20-30% of cat and dog allergic patients show IgE reactivity and mount IgE-mediated allergic reactions to cat and dog albumin. It is astonishing that allergic patients can develop specific IgE responses against animal albumins because these proteins exhibit a more than 70% sequence identity to human serum albumin (HSA) which is the most abundant protein in the blood of the human body. Sequence identity of cat albumin (Fel d 2) and dog albumin (Can f 3) and HSA is 82% and 80%, respectively. Given the high degree of sequence identity between the latter two allergens and HSA one would expect that immunological tolerance would prohibit IgE sensitization to Fel d 2 and Can f 3. Here we discuss two possibilities how IgE sensitization to Fel d 2 and Can f 3 may develop. One possibility is failed development of immune tolerance in albumin allergic patients whereas the other possibility is highly selective immune tolerance to HSA but not to Fel d 2 and Can f 3. If the first assumption is correct it should be possible to detect HSA-specific T cell responses and HSA-containing immune complexes in sensitized patients. In the latter scenario few differences in the sequences of Fel d 2 and Can f 3 as compared to HSA would be responsible for the development of selective T cell and B cell responses towards Fel d 2 as well as Can f 3. However, the immunological mechanisms of albumin sensitization have not yet been investigated in detail although this will be important for the development of allergen-specific prevention and allergen-specific immunotherapy (AIT) strategies for allergy to albumin.